High-yield debt covenants and their real effects - Falk Bräuning; Victoria Ivashina; Ali Ozdagli (Federal Reserve Bank of Boston, 2022)
High-yield debt, including leveraged loans, is characterized by incurrence financial covenants, or "cov-lite" provisions. Unlike, traditional, maintenance covenants, incurrence covenants preserve equity control rights but trigger pre-specified restrictions on the borrower's actions once the covenant threshold is crossed. We show that restricted actions impose significant constraints on investments: Similar to the effects of the shift of control rights to creditors in traditional loans, the drop in investment under incurrence covenants is large and sudden. This evidence suggests a new shock amplification mechanism through contractual restrictions that are at play for a highly levered corporate sector long before default or bankruptcy.
Keywords: G31; G33; G21; G32; 330; high-yield debt; corporate debt; covenants; incurrence covenants; cov-lite; amplification mechanisms; contracts; contingent contracting